The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0102-86502008000700018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of colon-cleansing methods in preparation for colonoscopy - Comparative efficacy of solutions of mannitol, sodium picosulfate and monobasic and dibasic sodium phosphates

Abstract: PURPOSE: Colonoscopy plays an essential role in the therapeutic and diagnostic approach in various colonic pathologies, the aim of the present study was to compare three solutions and their efficacy for the bowel preparation in adult patients submitted to elective colonoscopy. METHODS: Sixty patients were randomly divided into three groups of 20 each. Each group was submitted to a bowel preparation with one of the following solutions: 10% manitol, sodium picosulphate or sodium phosphate. The parameters evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…1,12 Nevertheless, to be an test of excellence, the quality of the preparation is a determining factor, since patients whose preparation is regular have the effectiveness of their test affected, leading to an increase in costs and also a lower polyp detection rate. 11,12 Furthermore, solutions should be safe and e with acceptable patient tolerance. 15 Our results suggest that the ingestion of any of the four types of preparation is equally effective as for the quality of the cleansing of the colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,12 Nevertheless, to be an test of excellence, the quality of the preparation is a determining factor, since patients whose preparation is regular have the effectiveness of their test affected, leading to an increase in costs and also a lower polyp detection rate. 11,12 Furthermore, solutions should be safe and e with acceptable patient tolerance. 15 Our results suggest that the ingestion of any of the four types of preparation is equally effective as for the quality of the cleansing of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, this solution is widely used in Brazil, since it is considered as a good intestinal preparation method, with the best cost and with appropriate effectiveness and safety. 1,11 Lactulose, nonabsorbable disaccharide, which undergoes bacterial action, was chosen as intestinal preparation because it is widely available, affordable costs and with effectiveness results similar to those of mannitol. 12 Lactitol, as well as lactulose, have both been used as options of intestinal preparation with good results reported by the manufacturer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only recently commercially specific colon cleansing products for colonoscopy have become available in Brazil. Several studies have reported on the use of mannitol in Brazil, demonstrating effectiveness in colon preparation, good tolerability and very low complication rates (3,11,16,17,19,24,27) . Methane production in the bowel is poorly understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol is a polyalcohol obtained by hydrogenating fructose from sucrose. It is a commonly used osmotic laxative associated with successful colonic cleansing compared to other solutions, although it is related to adverse events in more than 10% of cases (nausea, vomiting, headache, dehydration, and hypovolemia) [14][15][16]. Polyethylene glycol (polyethylene glycol [PEG]) has a molecular weight greater than 3,000 kDa and functions as a non-absorbable osmotic agent, retaining water molecules through hydrogen bonds; it is considered a good option for bowel preparation [14,15,17].…”
Section: Introductionmentioning
confidence: 99%